Pengaruh Informasi Akuntansi Terhadap Harga Saham pada Perusahaan Manufaktur - Sulis Mardiyanto; Yuli Tri Cahyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of Earnings Per Share (EPS), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Price Book Value (PBV) on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The research employs a quantitative method with secondary data sourced from the companies’ financial statements published on the IDX official website. The sample is selected using purposive sampling with criteria that include companies that publish complete financial statements, use Rupiah as their currency, and report profits during the study period. The analysis technique used is multiple linear regression. The results indicate that EPS significantly affects stock prices, while NPM, DER, and PBV do not show significant influence.